Chronic Galeazzi Fracture-Dislocation: A Case Report - Alajmi, Turki Abdullah S. (J Orthop Case Rep, 2020)
INTRODUCTION: Galeazzi fracture-dislocation is a unique entity of forearm fractures since they involve a fracture of the radius shaft, along with the dislocation of the distal radioulnar joint, the gold standard of treatment for adults is open reduction and internal fixation with or without repair or pinning of the DRUJ. CASE REPORT: We present a case of a 27-year-old male with a neglected Galeazzi fracture for over 2 months, the patient was treated with open reduction and internal fixation without the need of a salvage procedure and achieved excellent outcomes. CONCLUSION: Galeazzi fractures are not uncommon, and any forearm fracture requires complete radiographic and clinical assessment to avoid dreadful complications of delayed management.